Development of a high-performance tactile feedback display for three-dimensional shape rendering. (6th September 2019) - Zhang, Zhen; Lu, Xin; Hagihara, Yoshihiro; Yimit, Adiljan
This article presents a virtual tactile display using a shape-displaying method with flexible tendon-driven transmission to enhance performance. Sixteen tactors move perpendicularly in a 4 × 4 module to render the local shape of the virtual object to the skin of the user's fingertip. We detail the display structure design and the transmission system, and we combine the compact design of the drive unit and tactor module with a flexible tendon-driven transmission to address the ergonomic constraints on previous devices and make them more suitable for tactile feedback. In this work, we integrate the display with leap motion controller and a ray detection rendering method to generate tactile feedback. To evaluate the performance, we perform a virtual touch experiment that assesses how much the display can render the surface of three-dimensional objects to aid the participant to match the tactile sensation with visual stimuli in the virtual scene. Results show that the display improves the user experience and has good feasibility and effectiveness. In addition, the portable structure allows the user's hand to move more freely without redundant restrictions, and the larger tactor amplitude provides more shape patterns than previous models.